The role of epigenetic modulators on circadian rhythms and metabolism - Mosneagu, DI (2021)
The earth’s rotation on its axis with a 24-hour period gave rise to circadian rhythms, which originated pervasive biologic fluctuations in gene expression, cellular physiology and whole-organism behaviour. The advancements in technology and culture accentuated behaviours and phenomena that implicated a disruption in the synchronisation between our inner circadian clock and the outer environment. This desynchrony was associated with a deregulated molecular clock and an increased incidence of metabolic disorders. We have identified circadian rhythm enhancers as a potential chronotherapeutic mechanism in tackling the circadian deregulations that could be key in the pathogenesis of these associated metabolic deregulations.